Primary cutaneous B-cell lymphoma (non-leg type) has excellent outcomes even after very low dose radiation as single-modality therapy. Issue 1 (2nd January 2016) - Akhtari, Mani; Reddy, Jay Paul; Pinnix, Chelsea C.; Allen, Pamela K.; Osborne, Eleanor M.; Gunther, Jillian R.; Milgrom, Sarah A.; Smith, Grace L.; Wogan, Christine F.; Fowler, Nathan; Rodriguez, Maria Alma; Dabaja, Bouthaina
Abstract : Primary cutaneous B cell lymphomas (PCBCL) are rare; although data on outcomes and treatment are limited, traditionally they have been treated with radiation doses in excess of 24 Gy. We retrospectively identified and reviewed all cases of PCBCL treated at our institution from 2002–2014. Thirty-nine patients with PCBCL (42 lesions) were identified. Radiation was the only treatment for most patients. All lesions had a complete response and none had in-field failures; seven patients had out-of-field relapses, three of which were salvaged with radiation therapy. No differences in PFS or OS were found for patients given low-dose (≤ 12 Gy) versus high-dose (> 12 Gy) radiation. PCBCL is an indolent entity with a long clinical course and excellent response to radiation therapy and successful salvage of recurrent disease, even when doses are as low as 4 Gy. Given the above findings, we recommend the initial use of low-dose irradiation for PCBCL.